Caracterización Morfológica del Lagomorfo Silvestre Ecuatoriano en la Provincia de Cotopaxi. - Núñez Toscano, Félix Emiliano (2018)
The present investigation was carried out in Cotopaxi province, Latacunga Canton, Cusubamba, and Mulalillo Parishes, located at 3600 meters above sea level, characterized by low temperatures, almost constant throughout the year, with a lot of rains. The project was done with the objective to characterize the morphology of the Ecuadorian wild lagomorph in the Cotopaxi province. 30 animals were used (15 males and 15 females). Zoometric measurements were taken with the use of a measuring tape, a ruler and a square. The calculation of means and the standard deviation was carried out, phenotypic and morphometric characters were evaluated. Within the morphometric parameters we have in cm: rose to the cross of 8.98, with a lifted to the moths 10.48, height to the sternum 3.39, cm length of the head 8.79, a width of the head 8,48, length of the face 8.78, a diameter of the snout 12.05, bicoastal diameter 27.93, longitudinal diameter 34.62, diameter sternal back 34.62, thoracic perimeter 23.45, length of the leg 4.09, length of the hand 8.14, length of the rump 5.21, a width of the rump 5.79, hair length 2.17, weight 852.67 grams, they were the most relevant morphometric parameters. The shape of a head, shape of the rounded ears, arched type. Convex frontonasal cephalic profile, The orientation of the erect ears, Size of the medium ears. The color of the coat and the chinchilla layer is brown. The color of the darkened mucous membranes, the nails are dark colored, the eyes are black. They have evolved fur. The males had bigger size in their structures compared to the females; there were no differences between the lagomorphs of the Mulalillo and Cusubamba parishes. It was compared with other species of rabbits determining that one of greater proportions and greater size is the giant of Flander, followed of the New Zealander, the head of the lion and the smaller one in all the aspects the wild lagomorph